The Effect of Profitability and Capital Structure on Stock Returns with Earnings Management as an Intervening Variable: Study on Food and Beverage Subsector Companies Listed on the Indonesia Stock Exchange 2012-2021 - Gusmiarni (LPPM STIE PPI, 2024)
Introduction/Main Objectives:. To test the effect of Profitability and Capital Structure on Stock Returns with Earnings Management as an Intervening Variable. Background Problems: The performance of the food and beverage industry during the 2015-2019 period grew by an average of 8.16%, investment realization in the manufacturing sector reached IDR 1,348.9 trillion with the most popular and promising main sector being the Food Industry. Novelty: Adding intervening variables to the test and testing the direct and indirect effects on the Food and Beverage industry. Research Methods: Quantitative with secondary data types in the form of financial reports obtained from the Indonesia Stock Exchange website. Findings/Results: Profitability has no effect on Earnings Management, Capital structure has an effect on Earnings Management, Profitability has an effect on Stock Returns, Capital structure and earnings management have no effect on Stock Returns and partially show that Earnings Management is unable to mediate the effect of Profitability and Capital structure on Stock Returns. Conclusion: Always look at financial reports (fundamentals) from various aspects, not only looking at the size of profitability and capital structure, this is to get more accurate information.